Assessment of interatomic parameters for the reproduction of borosilicate glass structures via DFT‐GIPAW calculations. Issue 12 (25th June 2019) - Fortino, Mariagrazia; Berselli, Alessandro; Stone‐Weiss, Nicholas; Deng, Lu; Goel, Ashutosh; Du, Jincheng; Pedone, Alfonso
Abstract: Borates and borosilicates are potential candidates for the design and development of glass formulations with important industrial and technological applications. A major challenge that retards the pace of development of borate/borosilicate based glasses using predictive modeling is the lack of reliable computational models to predict the structure‐property relationships in these glasses over a wide compositional space. A major hindrance in this pursuit has been the complexity of boron‐oxygen bonding due to which it has been difficult to develop adequate B–O interatomic potentials. In this article, we have evaluated the performance of three B–O interatomic potential models recently developed by Bauchy et al [ J . Non‐Cryst. Solids, 2018, 498, 294–304], Du et al [ J. Am. Ceram. Soc. https://doi.org/10.1111/jace.16082 ] and Edèn et al [ Phys. Chem. Chem. Phys., 2018, 20, 8192–8209] aiming to reproduce the short‐to‐medium range structures of sodium borosilicate glasses in the system 25 Na2 O x B2 O3 (75 −  x ) SiO2 ( x  = 0‐75 mol%). To evaluate the different force fields, we have computed at the density functional theory level the NMR parameters of 11 B, 23 Na, and 29 Si of the models generated with the three potentials and the simulated MAS NMR spectra compared with the experimental counterparts. It was observed that the rigid ionic models proposed by Bauchy and Du can both reliably reproduce the partitioning between BO3 and BO4 species of the investigated glasses, along with the local environment around sodium in the glass structure. However, they do not accurately reproduce the second coordination sphere of silicon ions and the Si–O–T (T = Si, B) and B‐O‐T distribution angles in the investigated compositional space which strongly affect the NMR parameters and final spectral shape. On the other hand, the core‐shell parameterization model proposed by Edén underestimates the fraction of BO4 species of the glass with composition 25Na2 O 18.4B2 O3 56.6SiO2 but can accurately reproduce the shape of the 11 B and 29 Si MAS‐NMR spectra of the glasses investigations due to the narrower B–O–T and Si‐O‐T bond angle distributions. Finally, the effect of the number of boron atoms (also distinguishing the BO3 and BO4 units) in the second coordination sphere of the network former cations on the NMR parameters have been evaluated.